Membentuk Insan Kamil Melalui Tazkiyatun Nafs (Tinjauan Psikoterapi Islam) - Bayu Dwi Apriliani; Syamsul Arifin (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Tazkiyatun nafs, which etymologically means the purification of the soul, is understood as a process of spiritual and moral development aimed at shaping a complete human personality in accordance with the values of tawhid. This study aims to analyze the concept of tazkiyatun nafs as an Islamic psychotherapeutic approach in forming the insan kamil through a comprehensive literature review. This study employs a literature review method by examining various classical and contemporary sources, including works of Sufi scholars, Muslim psychologists, and Islamic psychotherapy literature. The findings indicate that tazkiyatun nafs consists of systematic stages, including mujahadah (earnest striving), muraqabah (self-awareness under Allah’s supervision), muhasabah (self-reflection), and riyadhah an-nafs (disciplining the soul), all of which function collectively as spiritually based psychotherapeutic techniques. This process is proven to be relevant in forming the insan kamil, namely individuals who achieve moral perfection, emotional stability, inner tranquility, and moral integrity. The study concludes that tazkiyatun nafs is an effective Islamic psychotherapeutic approach for character development and holistic mental well-being, particularly within the context of modern society facing psychological challenges and spiritual crises. This study is expected to contribute to the development of more applicable Islamic psychotherapy models in guidance and counseling.